A Survey on Oral Health Condition in Primary School Children - Fakir, Mohammad Masum; Ul Alam, Kazi Mehdih; Al-Mamun, Fakir; Sarker, Nazia (Medicine Today, 2012)
This Study was carried out to evaluate the dental health condition in primary school going children (Class iii to class v) age group in 8 to 12 years, in the school named Mughda high school in Dhaka City. This cross sectional study was carried out during the month of July 2009. Data was collected by pre-set questionaire of 183 students. The following observations were made when the results were compared between: 1. Total Number of decaied, caries or missing teeth found in the children mouth involving only in Permanent teeth. 2. Total Number of decaied, caries or missing teeth found in the individuals mouth. involving only in deciduous teeth. From this analysis we found the actual statistical analysis of oral heath condition of the patients teeth in between the age of 8 to 12 years. And also impact of tooth brushing and contributing factors that results decay of the teeth and destruction of gingival tissue. Medicine Today 2010 Volume 22 Number 02 Page 70-71 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12436